Skin Interstitial Fluid and Plasma Multiplex Cytokine Analysis Reveals IFN-γ Signatures and Granzyme B as Useful Biomarker for Activity, Severity and Prognosis Assessment in Vitiligo - Ng, Chau Yee; Chiu, Yen-Chuan; Chan, Yu-Pei; Lin, Yu-Jr; Chung, Pei-Han; Chung, Wen-Hung; Ku, Cheng-Lung (Frontiers in Immunology, 2022)
Background: The course of vitiligo is unpredictable, with periods of disease flare-ups and prolonged recovery periods. It is essential to establish a biomarker profile as a substitute marker for disease activity to predict disease activity, severity, and prognosis prediction. The use of localized skin interstitial fluid as biomarkers has recently gained interest, but extensive studies of the association between skin interstitial fluid, plasma, and the disease course is lacking. The aim of this study is to evaluate the cytokine expression profiles in the skin and plasma and the utility of the biomarker panel in assessing disease activity, severity, and prognosis in patients with vitiligo. Methods: In this prospective cohort study, 86 patients, and 34 healthy controls were recruited from the outpatient department of a tertiary medical center from March 2019 to September 2021. All patients were of Asian ethnicity. Two independent investigators evaluated disease activity and severity with longitudinal follow-ups for treatment response for a twelve-month period. Ultrasensitive multiplex cytokine panel with single-molecule counting technology immunoassays were used to study the cytokine expression in skin interstitial fluid and plasma. Results: IFN-γ and signature cytokines, including CXCL9, CXCL10, and GzmB, are most highly expressed in the vitiligo patients' lesion skin interstitial fluid and plasma compared to healthy control. By way of comparison, no significant changes in IL1b, IL13, IL15, IL17a, IL18 were observed. Receiver operating characteristic analysis revealed that IFN-γ is the most sensitive and specific marker in predicting disease activity, followed by CXCL10 and Granzyme B. CXCL9 was sensitive and specific in diagnosing vitiligo disease severity. The decrease in IFN-γ expression level is positively correlated with the treatment response. Conclusion: IFNγ, CXCL9, CXCL10, and GzmB are highly expressed in vitiligo patients' lesion skin and plasma and may serve as biomarkers for the clinical activity, severity, and prognosis prediction in vitiligo patients. Among all, IFN-γ exerts the highest predictive value in disease activity and treatment response, supporting the critical role of IFN-γ in the pathogenesis of vitiligo.